The cost of care for children hospitalised with Invasive Group A Streptococcal Disease in Australia - Natasha K. Brusco; Jane Oliver; Alissa McMinn; Andrew Steer; Nigel Crawford (BMC, 2021)
Abstract Background Invasive Group A Streptococcal (iGAS) disease exerts an important burden among Australian children. No Australian hospitalisation cost estimates for treating children with iGAS disease exist, so the financial impact of this condition is unknown. Aim To determine the minimum annual healthcare cost for children (< 18 years) hospitalised with iGAS disease in Australia from a healthcare sector perspective. Methods A cost analysis including children with laboratory-confirmed iGAS disease hospitalised at the Royal Children's Hospital (Victoria, Australia; July 2016 to June 2019) was performed. Results were extrapolated against the national minimum iGAS disease incidence. This analysis included healthcare cost from the 7 days prior to the index admission via General Practitioner (GP) and Emergency Department (ED) consultations; the index admission itself; and the 6 months post index admission via rehabilitation admissions, acute re-admissions and outpatient consultations. Additional extrapolations of national cost data by age group, Aboriginal and Torres Strait Islander ethnicity and jurisdiction were performed. Results Of the 65 included children, 35% (n = 23) were female, 5% (n = 3) were Aboriginal and Torres Strait Islander, and the average age was 4.4 years (SD 4.6; 65% aged 0-4). The iGAS disease related healthcare cost per child was $67,799 (SD $92,410). These costs were distributed across the 7 days prior to the index admission via GP and ED consultations (0.2 and 1.1% of total costs, respectively), the index admission itself (88.7% of the total costs); and the 6 months post index admission via rehabilitation admissions, acute re-admissions and outpatient consultations (5.3, 4.5 and 0.1% of total costs, respectively). Based on a national minimum paediatric incidence estimation of 1.63 per 100,000 children aged < 18 (95%CI: 1.11-2.32), the total annual healthcare cost for children with iGAS in 2019 was $6,200,862. The financial burden reflects the overrepresentation of Aboriginal and Torres Strait Islander people in the occurrence of iGAS disease. Costs were concentrated among children aged 0-4 years (62%). Conclusion As these cost estimations were based on a minimum incidence, true costs may be higher. Strengthening of surveillance and control of iGAS disease, including a mandate for national notification of iGAS disease, is warranted. Trial registration The current study is a part of ongoing iGAS surveillance work across seven paediatric health services in Australia. As this is not a clinical trial, it has not undergone trial registration.